Investigating cybercrimes under the Malaysian cyberlaws and the criminal procedure code: issues and challenges - Mohamed, Duryana (LexisNexis, 2012)

(untitled)
Investigating cybercrimes requires full commitment and readiness to fight the criminals. This means the investigating officer or any authorised person must not only have good knowledge and skills to detect the suspect and investigate cases of cybercrimes but he must also be ready to face the consequences. In this regard, having good procedural laws and adequate statutory provisions are very important to face the challenges ahead. To ensure the smooth running of investigation process, it is very important that the rules of procedures and certain standards of practice are complied with. This paper will discuss the process of investigating cybercrimes under the Malaysian cyberlaws and the Criminal Procedure Code ('CPC') with the aim to identify any inadequacies and challenges faced by the investigators. The main reference would be the Computer Crimes Act 1997, the Communications and Multimedia Act 1998 and the Criminal Procedure Code. Other laws will also be referred to as background information.